Knowledge sharing among undergraduate students in UiTM Puncak Perdana Campus / Elsy Awing - Awing, Elsy (Faculty of Information Management, 2010)
The purpose of this study is to investigate the factors that influence knowledge sharing among undergraduate students in UiTM Puncak Perdana campus. The factors covered the purpose and motivate for knowledge sharing, the type of knowledge shared, communication channels used and barriers in knowledge sharing. A questionnaire was used for collecting data. There were 150 students from the campus who participated in this study. It was found that obviously students have positive attitude toward knowledge sharing in the university environment. The students always shared study related matters among them as they were in an academic environment and often using face to face interaction in delivering knowledge with each other. However, the respondents were less inclined that lack of in depth relationships is the main barrier towards knowledge sharing that was graded. The study revealed that afraid to provide wrong knowledge is the major factor that inhibits knowledge sharing among them. Developing the culture of knowledge sharing is important in the university environment and it will make the sharing more effectiveness and meaningful to all communities in the university, especially the students.